ELECTROPHORETIC DETERMINATION OF AMYLASE IN THE POST-EMBRYONIC STAGE OF LABEO ROHITA (HAM.) - Das, B C (Indian Journal of Fisheries, 2011)
Work on enzyme synthesis, carried out in bacteria, shows that it is not only genetically determined but also influenced by culture conditions (Levinthal, 1959). The culture conditions presumably alter the rate at which the exogenous inducer enters the cell, the actual rate of synthesis being a function of the concentration of the inducer inside the cell (Hogness, 1959). The present research is the first to evaluate the amount of amylase present in post-embryonic Indian freshwater carp and to determine the influence of exogenous yeast Saccharomyces cerevisiae on amylase synthesis in the post-embryonic carp.